Current situation and influencing factors of palliative care practice ability among oncology nurses: A multicenter cross-sectional study - Xiaofei Nie; Fanfan Lv; Longti Li; Jia Jia (International Journal of Nursing Sciences)
Objectives: The study aimed to survey the current situation and explore the factors that influence the ability of palliative care practice among oncology nurses. Methods: A multicenter cross-sectional study was conducted using stratified random sampling to select 26 tertiary hospitals’ oncology departments in Hubei Province, China. A total of 1,198 nurses were included and finished the questionnaire consisting of social demographic characteristics, Palliative Care Self-Report Practice Scale (PCPS), End-of-life Professional Caregiver Survey (EPCS), and Self-Perceived Pain Assessment Knowledge and Confidence Scale (Self-PAC) through the online platform. Data were analyzed using t-test, one-way ANOVA, Pearson correlation analysis, and multiple linear regression analysis in SPSS 26.0. Results: The total score for PCPS was 67.17 ± 12.57, the three dimensions’ scores were: physical symptom care (32.50 ± 6.10), spiritual and psychological care (23.35 ± 4.97), communication (11.58 ± 2.48). There are significant positive correlations between the palliative care practice ability and core competence (r = 0.77, P < 0.01), as well as pain assessment ability (r = 0.56, P < 0.01). Multiple regression analysis identified female, with high education background (bachelor’s degree and master’s degree or above), interest in palliative care, pain assessment ability, and core competence were positive predictors of palliative care practice ability (Adjusted R2 = 0.668, P < 0.05). Conclusions: The overall ability of the oncology nurses to practice palliative care was relatively high, but the palliative nurses reported suboptimal performance in the communication dimension of palliative nursing practice ability. To comprehensively improve oncology nurses’ palliative care practice ability, managers must consider the gender structure, educational background, enthusiasm for palliative care work, core competence, and pain assessment ability.